Electrophysiological indices of target and distractor processing in visual search - Hickey, Clayton; Di Lollo, Vincent; McDonald, John J (Journal of cognitive neuroscience, 2009)
Attentional selection of a target presented among distractors can be indexed with an event-related potential (ERP) component known as the N2pc. Theoretical interpretation of the N2pc has suggested that it reflects a fundamental mechanism of attention that shelters the cortical representation of targets by suppressing neural activity stemming from distractors. Results from fields other than human electrophysiology, however, suggest that attention does not act solely through distractor suppression; rather, it modulates the processing of both target and distractors. We conducted four ERP experiments designed to investigate whether the N2pc reflects multiple attentional mechanisms. Our goal was to reconcile ostensibly conflicting outcomes obtained in electrophysiological studies of attention with those obtained using other methodologies. Participants viewed visual search arrays containing one target and one distractor. In Experiments 1 through 3, the distractor was isoluminant with the background, and therefore, did not elicit early lateralized ERP activity. This work revealed a novel contralateral ERP component that appears to reflect direct suppression of the cortical representation of the distractor. We accordingly name this component the distractor positivity (P(D)). In Experiment 4, an ERP component associated with target processing was additionally isolated. We refer to this component as the target negativity (N(T)). We believe that the N2pc reflects the summation of the P(D) and N(T), and that these discrete components may have been confounded in earlier electrophysiological studies. Overall, this study demonstrates that attention acts on both target and distractor representations, and that this can be indexed in the visual ERP.